2017
DOI: 10.3389/fnmol.2017.00097
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Functions of the β-Site Amyloid Precursor Protein Cleaving Enzyme 1 and 2

Abstract: BACE1 was discovered as the β-secretase for initiating the cleavage of amyloid precursor protein (APP) at the β-secretase site, while its close homology BACE2 cleaves APP within the β-amyloid (Aβ) domain region and shows distinct cleavage preferences in vivo. Inhibition of BACE1 proteolytic activity has been confirmed to decrease Aβ generation and amyloid deposition, and thus specific inhibition of BACE1 by small molecules is a current focus for Alzheimer’s disease therapy. While BACE1 inhibitors are being tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 163 publications
(225 reference statements)
1
95
0
Order By: Relevance
“…The proteolytic cut occurs within the extracellular or luminal juxtamembrane (membrane‐proximal) region or within the TM anchor of a membrane protein substrate. Cleavage sites within the juxtamembrane region are typically at a short distance of often 10 ‐ 35 amino acids from the TM segment, but more distant cleavage sites are possible and, in fact, the exact cleavage sites have only been determined for few shedding substrates (e.g., summarized for ADAMs and BACE1 in Caescu et al , ; Yan, ).…”
Section: Definition Of Ectodomain Sheddingmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteolytic cut occurs within the extracellular or luminal juxtamembrane (membrane‐proximal) region or within the TM anchor of a membrane protein substrate. Cleavage sites within the juxtamembrane region are typically at a short distance of often 10 ‐ 35 amino acids from the TM segment, but more distant cleavage sites are possible and, in fact, the exact cleavage sites have only been determined for few shedding substrates (e.g., summarized for ADAMs and BACE1 in Caescu et al , ; Yan, ).…”
Section: Definition Of Ectodomain Sheddingmentioning
confidence: 99%
“…The proteolytic cut occurs within the extracellular or luminal juxtamembrane (membraneproximal) region or within the TM anchor of a membrane protein substrate. Cleavage sites within the juxtamembrane region are typically at a short distance of often 10 -35 amino acids from the TM segment, but more distant cleavage sites are possible and, in fact, the exact cleavage sites have only been determined for few shedding substrates (e.g., summarized for ADAMs and BACE1 in Caescu et al, 2009;Yan, 2017). Several other proteolytic events in cells, such as removal of a signal peptide by signal peptidase (Blobel & Dobberstein, 1975) and proteolytic cleavages by mitochondrial AAA proteases (Levytskyy et al, 2017), formally share similarities to ectodomain shedding, but will not be discussed in this review, as they occur either during protein biosynthesis but not on the mature protein (signal peptidase), or do not occur in the secretory or endocytic pathway (mitochondria).…”
Section: Definition Of Ectodomain Sheddingmentioning
confidence: 99%
“…It has been shown that BACE1 is normally expressed in broad brain regions, with rich expression by hippocampal granule cells. BACE1 has been shown to play a critical role in synaptic development and plasticity through cleavage of its various substrates [51, 53, 54]. The effects of BACE1 on synaptic functions are likely to be through multiple mechanisms, as discussed below.

BACE1 deficiency alters synaptic plasticity in relation to APP cleavage: Long-term changes in the strength of synaptic transmission are the basis of memory formation.

…”
Section: Effects Of Bace1 On Synaptic Functionsmentioning
confidence: 99%
“…The ratio of 1-19/amyloidogenics was significantly higher in T21 lines from the isogenic model, compared to its disomic isogenic control, and compared to DupAPP, but it was unchanged in the other two unrelated DS iPSC lines (see also Supplementary Information for a more detailed explanation). As the proportions of BACE2-unrelated α-site cleavage products (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) were not different between T21 and isogenic D21 organoids (in any of the 3 experiments) ( Fig. 1a), it can be predicted that the increased presence of 1-19, 1-20 and 1-34 peptides in T21 contributes towards an overall increase in soluble peptides that are non-amyloidogenic.…”
Section: Trisomy 21 (But Not Dupapp) Skews the Ratios Of Aβ Non-amylomentioning
confidence: 91%
“…BACE1 is the main β-secretase in the brain 9 , while the expression and function of its homologue BACE2 (encoded by a chromosome 21 gene) remain less clear 10,11 . At least 3 different activities of BACE2 were recorded with regards to APP processing: as an auxiliary β-secretase (proamyloidogenic), as a θ-secretase (degrading the β-CTF and preventing the formation of Aβ), and as Aβ-degrading protease (AβDP) (degrading synthetic Aβ-peptides at extremely acidic pH).…”
Section: Introductionmentioning
confidence: 99%